(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
Populations of Seseli lehmannii Degen, arare endemic plant, were studied in the Crimea with giving data on distribution, morphological, ecological features of the species, agestructure of population and reasons for decreasing number of individuals.